2007
DOI: 10.1063/1.2722786
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence dynamics in GaAs along an optically induced Mott transition

Abstract: Radiative recombination spectra of p -type δ -doped Ga As ∕ Al As multiple quantum wells near the Mott transitionWe present a detailed experimental study of the effects of the optically induced transition from the excitonic, insulating regime, to the plasma, metallic regime, on the spectra and on the photoluminescence dynamics of GaAs. The transition is rather abrupt and presents a Mott-like behavior. The critical temperature, of 49 K, corresponds to the exciton binding energy. Through the study of the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Such a determination is usually achieved based on an analysis of the PL spectra (see, for instance, Refs. [43][44][45] rather than on simple estimates using the energy fluence per pulse. However, the direct applications of these methods is hindered by the large broadening of the PL from the GaAs core of our nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…Such a determination is usually achieved based on an analysis of the PL spectra (see, for instance, Refs. [43][44][45] rather than on simple estimates using the energy fluence per pulse. However, the direct applications of these methods is hindered by the large broadening of the PL from the GaAs core of our nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…However, within a small region in the phase diagram at low exciton binding energy, we also find bistability, which would correspond to a sudden transformation of the exciton gas into the electron-hole liquid without phase-separation. We mentioned that experimentally there are both evidences of continuos exciton Mott transitions, i.e., phase separation [11,13,14,28], as well as of discontinuous ones [6,7,9,10,35,63,65]. The discriminant parameter might well be the exciton binding energy E ex , as we do find, since a discontinuous transition is mostly observed in bulk semiconductors, while a continuous one in confined geometries, like quantum wells, where E ex is supposedly larger.…”
Section: Discussionmentioning
confidence: 99%
“…With increasing excitation, (i) a decrease of the excitonic absorption peak, (ii) an increase of the linewidth and (iii) a weak shift of the exciton peak to lower energies appear. In [42], we have reported that this shift turns to higher energies, if the temperature is decreased down to T = 5 K. It is an advantage of our spectral investigation of the Mott transition in comparison with investigations of the dynamics of the PL in [32][33][34][35][36][37][38] that we are able to address single electron-hole pair states in the optical response over the whole spectrum. In order to analyze the spectra in more detail, we have marked the maximum and the half-maximum absorption at the exciton left part, which are considered in figure 7.…”
Section: Semiconductor Bloch Equations-the Spectral Approachmentioning
confidence: 93%
“…The unbroken interest in the experimental verification of the Mott transition manifests itself in a series of papers, where the buildup of excitons was investigated in the time-resolved photoluminescence (PL) [32][33][34][35][36][37][38]. Here, the question of how the optically induced coherent polarization is transferred into an incoherent exciton population was considered.…”
mentioning
confidence: 99%